The nose, toes and tummy book - Nicholls, Sally; Herba, Gosia (Great Britain : Andersen Press, 2024)
This is your nose. What happens when we press it? BEEEEP!From fingers that tickle to bellies that need to be gobbled up, join in with each family as they play their own games to name different bits of the body. From Waterstones Prize-winning Sally Nicholls comes this interactive book full of fun and play, illustrated with diverse young families by illustrator Gosia Herba.